ETHNIC RELATIONS AND HARMONIOUS COEXISTENCE THROUGH CROSS-CULTURAL MARRIAGE: ITS NEW PROSPECT IN THE GLOBAL AGE - Yoshida, Masanori (SOSIETAS, 2016)
It is said that the age of globalization of Japan started at 15century like other Western countries. It was the beginning of world-wide dispersal of the Japanese in history such as the trade by Wako ships to the Southeast Asia (Befu Harumi 2002). Since then, Japan entered the age of isolation by the Tokugawa Shogunate and closed the door for other countries except for the Dutch. The new age began after the American Black ships came to Japan at the end of 19th century. Japan accepted the foreign culture, especially western culture which was the aspiration of the Japanese in those days enthusiastically. However, it was through the experience of the overseas migration and the dispatch as soldiers at war and colonization that the general Japanese lived in and learned from the foreign culture directly.This paper considers ethnic relations and harmonious coexistence through cross-cultural marriage between Japanese and Indonesian nationals in the anthropological perspective. We asked how the couples crossed the cultural difference and how they obtained the harmony by maintaining their ethnicity in their daily life.The Japanese do not always recognize their ethnicity or culture in their daily life and are not aware of multiplicity of cultures in Japan. Once they meet with other culture, they start to recognize how to understand and how to live with other culture and people more seriously.I focus on the cross-cultural marriage because we can learn the process of learning, negotiating and understanding other culture and ethnicity based on the concrete data.